PEMEROLEHAN BAHASA ANAK USIA 3-4 TAHUN PADA TATARAN FONOLOGI (LANGUAGE ACQUISITION OF 3-4 YEAR OLD CHILDREN AT THE PHONOLOGICAL LEVEL) - Ardhia Nadin Patresia Panggabean; Natalia Margaret Nababan; Prisilia August Sabria Sitompul; Zahara Husni Zalfana; Anggia Puteri (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Language is the most important primary communication tool that allows humans to interact and share information with others. As a dynamic system, language is always evolving following changing times, this is marked by the emergence of new terms, variations in use and changes in meaning. In the context of children's language acquisition, early childhood is an important phase where linguistic development takes place significantly. This article aims to explore the theory of early childhood language acquisition by focusing on analysis at the levels of phonology, syntax and semantics. The discussion focuses on general patterns in phonological development such as the deletion or replacement of phonemes, children's syntactic abilities in producing various types of sentences, as well as semantic preferences for denotative meanings that are relevant to the environment. Social and environmental interactions play a big role in this process, so that appropriate stimulation becomes The key to enriching children's language skills. The method used in this article is literature study. This study is expected to provide theoretical insight into the dynamics of children's language acquisition, especially in the modern era which is full of communication challenges.